2019
DOI: 10.9734/jabb/2018/v20i330079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory, Analgesic and Antipyretic Potential of the Stem Barks Aqueous Extract of Albizia ferruginea (Guill. & Perr.) Benth. (Mimosaceae) in Rats and Mice

Abstract: Aims: The present research was carried out to investigate the anti-inflammatory, analgesic and antipyretic potential of aqueous extract of Albizia ferruginea stem bark. Place and Duration of Study: Department of Animal Biology and Physiology (Animal Physiology Laboratory), Faculty of Sciences, University of Yaoundé I. between March 2012 and June 2016. Methods: Qualitative and quantitative phytochemical analyzes were done.The anti-inflammatory effect of the plant extract (100 and 200 mg/kg) was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the regions of the Center, Coast and South of Cameroon, A. ferruginea is traditionally used for the treatment of several pathologies [6]. Indeed, previous pharmacological studies carried out on this plant have shown that the ethanol extract of A. ferruginea leaves corrects anemia [5] and the total aqueous extract of dry bark of A. ferruginea was able to reduce inflammation, pain and pyrexia [7]. A previous study on acute toxicity indicated that the DL50 of the total aqueous extract of dry bark of A. ferruginea would be greater than 5000 mg/kg [9] and this extract could be classified in category 5 of acute toxicity substances relatively low depending on the globally harmonized classification system (GHS) [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the regions of the Center, Coast and South of Cameroon, A. ferruginea is traditionally used for the treatment of several pathologies [6]. Indeed, previous pharmacological studies carried out on this plant have shown that the ethanol extract of A. ferruginea leaves corrects anemia [5] and the total aqueous extract of dry bark of A. ferruginea was able to reduce inflammation, pain and pyrexia [7]. A previous study on acute toxicity indicated that the DL50 of the total aqueous extract of dry bark of A. ferruginea would be greater than 5000 mg/kg [9] and this extract could be classified in category 5 of acute toxicity substances relatively low depending on the globally harmonized classification system (GHS) [10].…”
Section: Discussionmentioning
confidence: 99%
“…This plant has been used for years in traditional medicine for the treatment of several pathologies [6]. Previous pharmacological studies carried out on this plant showed that the ethanol extract of the leaves corrects anemia [5] and the aqueous extract of dry bark reduces inflammation, algia and pyrexia [7] as well as chronic inflammation in rats [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation